Research on the Prevention of Coal Blocking in Power Plant Raw Coal Bunker - XU Jinmiao; WU Afeng; LI Weike; FAN Xiaoru; FENG Lin (南方能源建设, 2019)
[Introduction] Coal blocking of pulverizing system is a big problem in power plant, especially for coal bunker. At present, there are many types of anti-blocking coal technologies on the market, but there are different opinions on the use effect. This paper aims to find a useful technology to prevent the coal anti-blocking. [Method] The paper studied the coal blocking reasons and same anti-blocking technologies, such as hyperbolic coal hopper, stainless steel hopper, hydraulic split board damper, reasonable design of falling coal pipe etc. The research focused on the technology of rotary blockage clearing machine. [Result] The results show that the technology has obvious effect on solving the problem of coal plugging in the coal bunker. But there are lubricating oil leakage at the joints between the static and dynamic parts, which shall be paid more attention on sealing selection. [Conclusion] The rotary blockage clearing machine technology in various anti-blocking coal technologies has obvious advantages and is worthy of popularization.The prevention of coal plugging in the pulverizing system is a comprehensive project. Regardless of the technology used, it is necessary to strengthen the scientific management of the coal source and coal yard to achieve the control of the moisture and viscosity of the coal into the furnace.